Peluang Investasi Emas Jangka Panjang Melalui Produk Cicil Emas BSI - Johny Budiman; Yulfiswandi Yulfiswandi; Florentina Jasmine; Kelvin Kelvin; Lovis Vernando (Universitas Hamzanwadi, 2023)
Indonesia's Islamic finance in recent years has shown a positive increase, supported by the majority of people who are Muslims so as to encourage the progress of the sharia industry, including sharia banking. One of the Islamic banking services is gold installment, which has become an investment choice during COVID-19 period. due to the relatively stable value of gold so as to avoid fluctuating rupiah values. This study aims to analyze the reasons investors make the decision to invest in gold installments in Islamic banks. The research was conducted using a qualitative method to produce a descriptive picture for the research. Data was collected using purposive sampling method through interviews with 3 sources from customers and management of Bank Syariah Indonesia. The results of the study show that service is one of the reasons for investing in gold installments. Easy, flexible procedures and a professional code of ethics make it comfortable for customers to invest. Another reason for investing in gold installments is product promotion, social influence from the people around who can determine decision making and personal goals of each individual.